RANCANG BANGUN APLIKASI AUGMENTED REALITY DENGAN METODE MARKERLESS BERBASIS ANDROID SEBAGAI MEDIA PROMOSI PARIWISATA DI KOTA TASIKMALAYA STUDI KASUS TAMAN WISATA KARANG RESIK - Luvi Zatnika, - (2020)
Most of tourism media promotion sites still use print media and social media, both of them are mostly in written form. To find out the information written, the user must read first so that information is delivered. Meanwhile, statistical data from UNESCO (United Nations Educational, Scientific and Cultural Organization) shows that Indonesian people have a low interest in reading which is ranked 60 out of 61 countries (Iswari, 2017). To overcome these problems, an application with augmented reality technology was made. According to Kurniawan Chandra Rahardja (Bayuaji, 2015), CEO of PT Interactive Indonesia Pratama, augmented reality technology is believed to change the dynamics of marketing with increasingly sophisticated and tangible tools, with a very broad application in various lines of business and industry.The purpose of the research is to design, build and testing the feasibility of the AR Aplication as a media promotion for the Karang Resik tourism park. In designing and building this application, it takes photos, layout, and the description of the vehicle. To process the data needed software namely blender and unity 2019. This AR application uses the markerless method, and the operating system used is the Android-based operating system, then for the application development method using the waterfall method. In this research, authors tested the application's feasibility level with the ISO 25010 testing method which consists of four aspects of testing, namely functional conformance testing with 100% results, compatibility testing with application results that can be run on 10 devices from 10 different devices. Testing the performance efficiency consists of three aspects with the results of which the thread access speed is an average of 77.5 seconds and an average CPU consumption of 11.3% and an average memory consumption of 532.1 mb, and usability testing with an average total result of 81%.